PROFIL KECEMASAN PADA INDIVIDU TERHADAP FENOMENA LINGKUNGAN - Purnomosidi, Faqih; Rifa’i, Fauzan; Rachmawati, Anniez (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2024)
Anxiety is all responses to threats that occur due to surrounding circumstances. Anxiety that cannot be handled properly will impact people’s health, whether psychological, physical or cognitive. Several factors that cause anxiety to appear in a person’s body are due to environmental phenomena, both the natural environment and the human environment. This research aims to determine the picture or profile of a person’s anxiety regarding environmental developments caused by human behavior or natural phenomena. The methodology in this research uses a qualitative phenomenology methodology, using interviews and observations of 6 informants. The results of this research are that every person who feels changes in nature due to human behavior such as logging which causes floods, the establishment of industries which cause air pollution, smoking behavior which causes air pollution and the phenomenon of unpredictable weather or climate changes can cause anxiety in a person so that Anxiety management is needed to prevent excessive feelings of anxiety